TcPho91 is a contractile vacuole phosphate sodium symporter that regulates phosphate and polyphosphate metabolism in Trypanosoma cruzi. Issue 5 (25th June 2015) - Jimenez, Veronica; Docampo, Roberto
Summary We have identified a phosphate transporter (TcPho91) localized to the bladder of the contractile vacuole complex (CVC) of Trypanosoma cruzi, the etiologic agent of Chagas disease. TcPho91 has 12 transmembrane domains, an N‐terminal regulatory SPX (named after SYG1, Pho81 and XPR1) domain and an anion permease domain. Functional expression in Xenopus laevis oocytes followed by two‐electrode voltage clamp showed that TcPho91 is a low‐affinity transporter with a Km for Pi in the millimolar range, and sodium‐dependency. Epimastigotes overexpressing TcPho91‐green fluorescent protein have significantly higher levels of pyrophosphate (PPi) and short‐chain polyphosphate (polyP), suggesting accumulation of Pi in these cells. Moreover, when overexpressing parasites were maintained in a medium with low Pi, they grew at higher rates than control parasites. Only one allele of TcPho91 in the CL strain encodes for the complete open reading frame, while the other one is truncated encoding for only the N‐terminal domain. Taking advantage of this characteristic, knockdown experiments were performed resulting in cells with reduced growth rate as well as a reduction in PPi and short‐chain polyP levels. Our results indicate that TcPho91 is a phosphate sodium symporter involved in Pi homeostasis in T. cruzi.